A Chromosome-Scale Reference Assembly of a Tibetan Loach, Triplophysa siluroides - Yang, Liandong; Wang, Ying; Wang, Tai; Duan, Shengchang; Dong, Yang; Zhang, Yanping; He, Shunping (Frontiers in Genetics, 2019)
Cobitoidea is one of the two superfamilies in Cypriniformes, however, few genome has been sequenced for Cobitoidea fishes. Here, we obtained a total of 252.90 Gb of short Illumina reads and 31.60 Gb of long PacBio Sequel reads, representing approximate genome coverage of 256× and 50×, respectively. The final assembled genome is about 583.47 Mb with contig N50 sizes of 2.87 Mb, which accounts for 91.44% of the estimated genome size of 638.07 Mb. Using Hi-C based chromatin contact maps, 99.31% of the genome assembly were placed into 25 chromosomes and the N50 is 22.3 Mb. The gene annotation completeness was evaluated by BUSCO, and 2,470 out of the 2,586 conserved genes (95.5%) could be found in our assembly. Repetitive elements were calculated to reach 33.08% of the whole genome. Moreover, we identified 25,406 protein-coding genes, of which 92.59% have been functionally annotated. This genome assembly will be a valuable genomic resource to understand the biology of the Tibetan loaches, and will also set a stage for comparative analysis of the classification, diversification, and adaptation of fishes in Cobitoidea.